Biochemical Status of Beta-Thalassemia Major Patients in Erbil City - Omar Surchi; Sarkawt Ali (Erbil Dental Journal)
Background and objectives: β -thalassemia major patient is one of the hereditary hemolytic diseases, which can cause many hematological and biochemical changes in the affected patient. And these changes can happen even when the patient is treated adequately. The objective was to study biochemical changes in the level of serum hepcidin, osteocalcin, calcium, ferritin, iron, PTH and IL-6 in patients with β- thalassemia major and to compare it with control subjects.